Legend (1986) [videorecording (DVD)] - Cruise, Tom, 1962-; Sara, Mia; Curry, Tim; Bennent, David; Playten, Alice; Barty, Billy; Hubbert, Cork, 1952-2003 (Universal Studios Home Entertainment, 2011)
A forest dweller is chosen to save a beautiful princess and defeat the Lord of Darkness in this visually stunning fantasy-adventure.